Electrophysiological Properties of Substantia Gelatinosa Neurons in the Preparation of a Slice of Middle-Aged Rat Spinal Cord - Li, Yang; Su, Shanchu; Yu, Jiaqi; Peng, Minjing; Wan, Shengjun; Ke, Changbin (Frontiers in Aging Neuroscience, 2021)
A patch-clamp recording in slices generated from the brain or the spinal cord has facilitated the exploration of neuronal circuits and the molecular mechanisms underlying neurological disorders. However, the rodents that are used to generate the spinal cord slices in previous studies involving a patch-clamp recording have been limited to those in the juvenile or adolescent stage. Here, we applied an N-methyl-D-glucamine HCl (NMDG-HCl) solution that enabled the patch-clamp recordings to be performed on the superficial dorsal horn neurons in the slices derived from middle-aged rats. The success rate of stable recordings from substantia gelatinosa (SG) neurons was 34.6% (90/260). When stimulated with long current pulses, 43.3% (39/90) of the neurons presented a tonic-firing pattern, which was considered to represent γ-aminobutyric acid-ergic (GABAergic) signals. Presumptive glutamatergic neurons presented 38.9% (35/90) delayed and 8.3% (7/90) single-spike patterns. The intrinsic membrane properties of both the neuron types were similar but delayed (glutamatergic) neurons appeared to be more excitable as indicated by the decreased latency and rheobase values of the action potential compared with those of tonic (GABAergic) neurons. Furthermore, the glutamatergic neurons were integrated, which receive more excitatory synaptic transmission. We demonstrated that the NMDG-HCl cutting solution could be used to prepare the spinal cord slices of middle-aged rodents for the patch-clamp recording. In combination with other techniques, this preparation method might permit the further study of the functions of the spinal cord in the pathological processes that occur in aging-associated diseases.